Досвід проектів Європейського Союзу з транскордонного співробітництва для України - Смик, Р. П.; Smyk, R. P. (Східноєвропейський національний університет імені Лесі Українки, 2014)
Cross-border cooperation as part of its policy , now occupies an important place in the priorities of the socioeconomic development and foreign policy, in particular the European integration of Ukraine. Scientific analys is of the theory and practice of cross-border cooperation especially Ukrainein the context of the European integration process is essential to the development and implementation of strategies of domestic and foreign policy of Ukraine today.
The experience of EU-funded cross-border cooperation for Ukraine
Роботу виконано на кафедрі міжнародної інформації СНУ ім. Лесі Українки